COMPUTER VISION BASED DETECTION FOR EARTHQUAKE WARNING USING HYDROPHONE - Idin, Nadialyn Binti; Azhar, NorHafizah Binti; Arkhiansyah, Yuni; -, Fitria (Prosiding International conference on Information Technology and Business (ICITB), 2018)
According to the recent earthquake and tsunami disaster in Sulawesi, Indonesia on 28 September 2018 with a strength of 7.4 Mw it has cost many lives and damage to the property. The number of victims of the tsunami deaths in Central Sulawesi, on October 10, 2018 at 13:00 pm, increased to 2045 people. The number consists of 1,636 people from Palu City, 171 from Donggala, Sigi 222 people, Parigi Moutong 15 people. The dark history that struck the population was the second catastrophic disaster in the Sulawesi region besides from the Tsunami Sulteng which took place on August 10, 1968, with magnitude 7.3 in Central Sulawesi. From that event, this disaster has become a starting point for creating a tool for detecting earthquake seismic activity by using Hydrophone. Hence, the purpose of this study is to proposed this tool to be used in the most threatening areas in Indonesia of such disaster. It will act to warn residents around the affected area to at least act to save themselves. Hydrophone is a microphone designed for underwater use to record or hear underwater sounds. Most Hydrophone is based on a piezoelectric transducer that generates electricity when it comes to pressure changes. Piezoelectric materials, or transducers, can convert sound signals into electrical signals because the sound is a pressure wave. It is hoped that this tool will be use in the future as it can save thousand or maybe million lives. Keywords: Sound Fixing and Raging (SOFAR); Marine Cable Hosted Observatory (MACHO); Short-time Fourier transform (STFT); Hadoop File System (HDFS); Marine Observatory in the Northeastern Taiwan; Central Weather Bureau (CWB);User Interface (UI);